2007
DOI: 10.2134/agronj2006.0205
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Maize Hybrids Respond Differently to Variations in Plant Density?

Abstract: Maize (Zea mays L.) grain yield responds greatly to plant density (D). However, the hybrid-plant density interaction usually found is not well understood. The objective of this work was to analyze responses of different maize hybrids to D considering their biomass plasticity and reproductive partitioning. Responses to D were ana-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
116
3
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(143 citation statements)
references
References 35 publications
13
116
3
11
Order By: Relevance
“…8, as well as from Sarlangue et al (2007) are not supportive of earlymaturing hybrids. In both studies, earliness was accompanied by lower yield per area potential and higher OP, i.e., stronger dependence on population.…”
Section: Current Crop Management Statusmentioning
confidence: 77%
See 4 more Smart Citations
“…8, as well as from Sarlangue et al (2007) are not supportive of earlymaturing hybrids. In both studies, earliness was accompanied by lower yield per area potential and higher OP, i.e., stronger dependence on population.…”
Section: Current Crop Management Statusmentioning
confidence: 77%
“…Improved prolificacy was regarded by Tokatlidis et al (2005) as the key factor for hybrids of low and broad OP. Sarlangue et al (2007) reported optimum for HI populations of 12.7 plants/m 2 for hybrid Romario that exhibited the lowest PYP, 10.6 plants/m 2 for hybrid P37P73 with an intermediate PYP, and only 6.5 plants/m 2 for the highest yielding at low population DK688. Boomsma et al (2009) discovered that strong responsiveness of grain yield per plant to reduced plant crowding accompanies higher HI values and better nitrogen use efficiency, suggesting a relatively high level of reproductive partitioning and plasticity.…”
Section: Environmental Yield Index (Eyi) and Crop Yield Potential (Cyp)mentioning
confidence: 94%
See 3 more Smart Citations